PENINGKATAN PENGETAHUAN K3 UNTUK PENCEGAHAN PENYAKIT AKIBAT KERJA PADA PETERNAK AYAM CIAMBAR - Hairunisa, Nany; Lestari, Ade Dwi; Ridwan, Alvin Mohamad; Ab. Razak, Asreene Binti; Putri, Fania Sabila; Syafitri, Julia Aina; Amirrudin, Danial Arif Bin; Asrani, Iffah syahidah Binti (Jurnal Pengabdian Masyarakat Trimedika, 2026)
Occupational diseases  remain a significant public health issue in various sectors, including small-scale poultry farming. In Ciambar Village, Sukabumi, chicken farmers are exposed to a variety of occupational hazards due to the absence of health evaluations and limited awareness of occupational health and safety. This community service program aimed to increase knowledge and awareness of occupational health and disease prevention among poultry farmers through educational counseling. The activity involved a health education session, supported by visual aids and interactive discussions. A pre-test and post-test were used to evaluate knowledge gain. Results showed a substantial increase in participants' knowledge, with post-test scores rising from 13% to 83%. These findings suggest that targeted educational interventions can significantly improve workers’ understanding of occupational hazards and encourage healthier work practices